2013
DOI: 10.11646/zootaxa.3630.3.8
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of oak gallwasp, Cyclocynips Melika, Tang & Sinclair (Hymenoptera: Cynipidae: Cynipini), with descriptions of two new species from Taiwan

Abstract: A new genus of cynipid oak gallwasp—Cyclocynips Melika, Tang, & Sinclair (Hymenoptera: Cynipidae: Cynipini), with two new species—C. uberis and C. tumorvirgae—reared from galls on oaks of the Quercus subgenus Cyclobalanopsis is described fromTaiwan. Descriptions of asexual generation adults and their diagnostic characters are presented. The likelihood of yet undiscovered sexual generations and the evolution of host-plant associations in these species are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Despite this relatively high species richness, little was known about cynipine galls on Cyclobalanopsis until the recent description of the genera Cycloneuroterus Melika &Cyclocynips Melika, Tang, &Sinclair, 2013 and new species of Plagiotrochus (Ide et al , 2012(Ide et al , 2013Melika et al 2013;Tang et al 2011aTang et al , b, 2016a. Only one cynipine species, Cycloneuroterus wangi Abe, Ide, & Odagiri, 2014, has been reported to oviposit on Cyclobalanopsis outside Japan, Taiwan and Vietnam despite the wide Asian distribution (Abe et al 2014) of this Quercus subgenus.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this relatively high species richness, little was known about cynipine galls on Cyclobalanopsis until the recent description of the genera Cycloneuroterus Melika &Cyclocynips Melika, Tang, &Sinclair, 2013 and new species of Plagiotrochus (Ide et al , 2012(Ide et al , 2013Melika et al 2013;Tang et al 2011aTang et al , b, 2016a. Only one cynipine species, Cycloneuroterus wangi Abe, Ide, & Odagiri, 2014, has been reported to oviposit on Cyclobalanopsis outside Japan, Taiwan and Vietnam despite the wide Asian distribution (Abe et al 2014) of this Quercus subgenus.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological and phylogenetic revisions support the division of the Cynipidae into several distinct tribes, within which the oak gall wasps (Cynipini) form a monophyletic assemblage (Liljeblad & Ronquist, 1998; Rokas et al ., 2002, 2003; Ronquist et al ., 2015). However, within the Cynipini, new genera and species are frequently being described (Pujade-Villar et al ., 2010; Medianero, Nieves-Aldrey & Melika, 2011; Ide et al ., 2012; Pujade-Villar et al ., 2012; Melika et al ., 2013; Tang et al ., 2016) and existing species and genera are often re-assigned making inferences into the biological characteristics of members of this group difficult (Drown & Brown, 1998; Melika & Abrahamson, 2007). While the vast majority of the oak gall wasps persist at low population level densities, due in part to regulation by parasitoids and inquilines (Washburn & Cornell, 1981; Moriya et al ., 1989; Stone et al ., 2002), occasionally species are known to outbreak and cause host plant damage and even mortality (Eliason & Potter, 2000; Cooper & Rieske, 2007; Pujade-Villar et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the Þrst gall-inducing wasp species observed on the subgenus Cyclobalanopsis was only described in 2010 , with a further 14 species described thereafter. In total, three species of Plagiotrochus Mayr, 1881, two species of Dryocosmus Giraud, 1859, seven species of Cycloneuroterus Melika & Tang, 2011, and two species of Cyclocynips Melika, Tang, & Sinclair, 2013 are currently known to be gall-inducing Cynipini on Cyclobalanopsis (Ide et al , 2012(Ide et al , 2013Tang et al 2011a,b;Melika et al 2013;Abe et al 2014). In addition, Synergus itoensis Abe, Wachi, & Ide, 2011, a member of the inquiline tribe Synergini, was also demonstrated to induce galls on Cyclobalanopsis (Abe et al 2011).…”
mentioning
confidence: 99%
“…In addition, Synergus itoensis Abe, Wachi, & Ide, 2011, a member of the inquiline tribe Synergini, was also demonstrated to induce galls on Cyclobalanopsis (Abe et al 2011). Although Cyclobalanopsis has a widespread distribution in Asia, the gall-inducing cynipids have been restricted to Japan, Taiwan, and Vietnam (Ide et al , 2012(Ide et al , 2013Abe et al 2011;Tang et al 2011a,b;Melika et al 2013;Abe et al 2014). Despite increasingly intensive taxonomic studies being conducted on Mainland China over the past decade (Melika et al 2004;Wang et al 2010Wang et al , 2012Wang et al , 2013Liu et al 2012;Pujade-Villar and Wang 2012;Bernardo et al 2013), no cynipid wasps associated with Cyclobalanopsis have been reported in this region to date.…”
mentioning
confidence: 99%